Japanese corporate governance and strategy: Adapting to financial pressures for change - William H. Lazonick (Levy Economics Institute of Bard College, 1998)
Despite the crisis in the Japanese financial sector, prolonged recession, and competitive challenges, Japan's formidable productive system remains strong. Nevertheless, the system of corporate governance, which has pursued a strategy of retaining corporate revenues and reallocating labor resources and returns to labor in order to invest in productive capabilities, faces short-term pressures from a transformation of the financial sector and long-term pressures from the growth of intergenerational dependence. Current reforms seek to generate funding for the pension system and profits for financial enterprises from international securities and money markets. These reforms seem to work within the corporate governance framework that emphasizes the retain-and-reallocate strategy, but the question is whether they will create powerful pressures to extract returns from the domestic economy, thereby affecting how corporations are managed and resources allocated.
Keywords: 330